Adaptive clinical trial of AZD7442 and SARS-CoV-2 vaccination in immunosuppressed patients highly vulnerable to infection with SARS-CoV-2 virus (RAPID-PROTECTION): protocol for a multicentre, interventional open-label, randomised controlled trial - Ernest Choy; Kerenza Hood; Emma Thomas-Jones; Eleanor Barnes; Keith Wilson; Christian H Ottensmeier; Debbie Harris; Adrian Hill; Mark Tuthill; Richard Adams; Catherine Porter; Katie Ewer; et al. (BMJ Open)
Introduction Despite repeated vaccinations against SARS-CoV-2 virus, patients who are immunocompromised remain at very high risk of catching SARS-CoV-2 virus and becoming unwell. AZD7442 (Evusheld) is a long-acting monoclonal antibody treatment that has been shown in clinical trials to prevent SARS-CoV-2 infection for up to a year after a single dose. Vaccines require a healthy immune system to generate protective immunity. AZD7442 may prevent SARS-CoV-2 infection in immunocompromised individuals that may not have responded to repeated vaccinations against SARS-CoV-2 virus. Unlike vaccinations, AZD7442 reaches effective levels within the body a few hours after a single dose. The RAPID-PROTECTION trial will determine the levels of immune protection that AZD7442 offers patients at the very highest risk of SARS-CoV-2 infection and whether this protection can be further enhanced by repeated vaccination against SARS-CoV-2 virus.Methods RAPID-PROTECTION is a multicentre, interventional and open-label adaptive platform trial that aims to recruit 350 immunocompromised participants across five UK centres. Participants will be administered AZD7442 on day 0 followed by a SARS-CoV-2 vaccination 28 days later. Participants will be randomised (1:1) to the Moderna vaccine or Pfizer/BioNTech vaccine. Participant samples will be taken at baseline and at multiple timepoints after the administration of AZD7442.Analysis The participant samples will be analysed to measure the function and magnitude of SARS-CoV-2 specific antibody and T-cell responses at baseline and at multiple timepoints after the administration of AZD7442. The immunological effect of the study interventions will be determined by comparison of the results of immunological assessments at baseline and subsequent timepoints.Ethics and dissemination The trial protocol was approved by the research ethics committee of the National Health Service (reference 22/HRA/0359), Health Research Authority and Health and Care Research Wales on 25 July 2022. Findings will be disseminated through peer-reviewed journals and presented at scientific conferences.Trial registration number ISRCTN53507177.